DESIGN AND DEVELOPMENT OF WEB-BASED APPLICATION CANGKINGAN USING SCRUM METHOD - Alim, Khori Sahirul; Ekowati, Nur Alfi; Kisworini, Rianti Yunita; Riyandari, Lutvi (Informatika, Universitas Jenderal Soedirman, 2023)
The web-based application can ease business owners on promoting and giving the services to the customers. Nevertheless, nowadays there are still not many UMKMs (micro, small, and medium enterprises) in the Banyumas Regency that apply it. Many of them still preserve the conventional way by doing the transaction directly. This research is aimed to design and develop a web-based marketplace application, namely Cangkingan. That application is supposed to help UMKMs in Banyumas in managing inventory, processing orders, and marketing culinary products online. The outline of this research flow includes needs analysis, system design, system development, and system testing. The methods of data collection that are used are interview, observation, literature study, and questionnaire. The application design is created in various diagrams and user interface designs. The method of system development is scrum. This design and development are done within 10 sprints in which each sprint is held for two weeks. The application is built using MySQL, CodeIgniter framework, and PHP language. Testing of Cangkingan system is carried out using the ISO 9126 standard which consists of testing functionality, usability, reliability, efficiency, portability, and maintainability. The test result on most of the test aspects state that the application is satisfactory (good). Especially for the usability testing that is done to 36 respondents, Cangkingan gets excellent result. This test result is one of the proofs that the research purpose has been achieved and the application Cangkingan that has been developed is able to help the UMKMs with culinary products in Banyumas.